Effect of Male Mating Time on Landrace Pig Reproduction - I Dewa Nyoman Sudita; Stefanus Nahak (Agriwar Journal, 2022)
Pig livestock is one of the livestock developed in Indonesia because it can adapt to environmental conditions, has good production and reproduction properties including fast growth so that the body matures and quickly, the number of liters of labor size is large, birth weight and weaning weight are high, meat production is high and can also meet human needs. To meet human needs for protein and the economy, it is necessary to increase the production and productivity of pig livestock by paying attention to reproductive aspects, and nutrition. This study aims to determine the influence of the time interval of male mating in nature which affects the conception rate, liter size, and mortality. This research was carried out in Catur Village, Kintamani District, Bangli Regency from April to August 2022. This study uses a quantitative descriptive method by mating males at time intervals and observing the results directly. The number of livestock used in this study was 6 landrace sows consisting of 1 sow mated with males at intervals of once a week, 2 heads mated at intervals twice a week, and 3 heads mated at intervals of three times a week. The variables observed in this study were conception rate, liter size, and mortality. The results showed that the interval of mating time influenced the conception rate value and the number of liters of size. The best interval from the results of this study is one mating in a week, namely a conception rate of 100%, the number of liters size 9 heads. And the time interval of mating has no effect on the mortality of the child at birth.